Mechanisms of Action of the KCa2-Negative Modulator AP30663, a Novel Compound in Development for Treatment of Atrial Fibrillation in Man - Bentzen, Bo Hjorth; Bomholtz, Sofia Hammami; Simó-Vicens, Rafel; Folkersen, Lasse; Abildgaard, Lea; Speerschneider, Tobias; Muthukumarasamy, Kalai Mangai; Edvardsson, Nils; Sørensen, Ulrik S.; Grunnet, Morten; Diness, Jonas Goldin (Frontiers in Pharmacology, 2020)
Aims: Small conductance Ca2+-activated K+-channels (SK-channels, KCa2) are a new target for treatment of atrial fibrillation (AF). AP30663 is a small molecule inhibitor of KCa2-channels that is currently in clinical development for treatment of AF. The aim of this study is to present the electrophysiological profile and mechanism of action of AP30663 and its efficacy in prolonging atrial refractoriness in rodents, and by bioinformatic analyis investigate if genetic variants in KCNN2 or KCNN3 influence the expression level of these in human heart tissue. Methods and Results: Whole-cell and inside-out patch-clamp recordings of heterologously expressed KCa2-channels revealed that AP30663 inhibits KCa2-channels with minor effects on other relevant cardiac ion channels. AP30663 modulates the KCa2.3 channel by right-shifting the Ca2+-activation curve. In isolated guinea pig hearts AP30663 significantly prolonged the atrial effective refractory period (AERP) with minor effects on the QT-interval corrected for heart rate. Similarly, in anaesthetized rats 5 mg/kg and 10 mg/kg of AP30663 changed the AERP to 130.7±5.4% and 189.9±18.6 of baseline values. The expression quantitative trait loci analyses revealed that the genome wide association studies for AF SNP rs13376333 in KCNN3 is associated with increased mRNA expression of KCNN3 in human atrial appendage tissue. Conclusions: AP30663 is a novel negative allosteric modulator of KCa2-channels that concentration-dependently prolonged rodent atrial refractoriness with minor effects on the QT-interval. Moreover, AF associated SNPs in KCNN3 influence KCNN3 mRNA expression in human atrial tissue. These properties support continued development of AP30663 for treatment of AF in man.